The shadows - West, Jacqueline, 1979- (West, Jacqueline, 1979- Books of Elsewhere, 2010)
When eleven-year-old Olive and her distracted parents move into an old Victorian mansion, Olive finds herself ensnared in a dark plan involving some mysterious paintings, a trapped and angry nine-year-old boy, and three talking cats.